The Effects of IFRS adoption on Accounting Quality: Evidence from China - Liu, Zheng (2009)
This paper is an empirical analysis of the accounting quality effects of IFRS adoption in China. I examined three proxies for accounting quality i.e. earnings management, timely loss recognition and value relevancy. The regression analyses cover the time period from 2003 to 2008 with 214 firms from Zhongzheng Index-300 and I sub-sampled all companies to State Owned Equities (SOEs) and Private Equities (PEs). Taken together, the results are mixed and vary between SOEs and PEs. The empirical analysis shows that SOEs’ earnings smoothing and timely loss recognition are improved, but their managing towards positive earnings and value relevancy are worsen; in the other hand, the earnings smoothing and value relevancy of PEs’ are improved significantly, but PEs’ managing towards positive earnings and timely loss recognition are both worsen after the IFRS adoption the. It also reveals that in terms of earnings management and timely loss recognition, the resulting figures for PEs’ in both pre-and-post-adoption periods are significantly better than that of SOEs’; and that PEs and SOEs are indifference in respect to the value relevance metric for pre and post IFRS adoption period.